On the Solvability of a Class of Nonlinear Integral Equations in Hölder Spaces. (12th March 2022) - Özdemir, İsmet
Abstract: In this paper, using the classical Schauder fixed point theorem, we prove that a nonlinear class of integral equations has at least one solution in the space of functions satisfying the Hölder condition. Also, some important examples showing the applicability of the existence theorem presented in this study are given.